Key Factors Shaping Satisfaction and Continued Use of MOOCs Among Computer Science Majors: Insights from Sichuan, China - Shanhong, Yang (Scholar: Human Sciences, 2025)
Purpose: This study determines how satisfied undergraduate computer science students are with using Massive Open Online Course (MOOCs) for learning at a science and technology university in Sichuan, China. The study establishes a theoretical framework comprising seven variables (information quality, confirmation, system quality, perceived ease of use, satisfaction, perceived usefulness, and continuance intention). Research Design, Data, and Methodology: A quantitative survey approach was employed to survey 500 undergraduate computer science students who had used MOOCs in their academic study for at least one year, utilizing a questionnaire as the primary instrument. Survey data were gathered through a multi-stage strategy involving judgment and quota sampling. Confirmatory factor analysis was used to evaluate the data to confirm the measurement model’s validity and ensure that each observed variable appropriately reflects its corresponding latent factor. Subsequently, additional structural equation modeling analyses are used to evaluate the measurement model’s accuracy, investigate the connections between the variables in the structural model. Results: The findings from the study supported the research assumptions, particularly in showing that continuance intention is significantly affected by satisfaction, with perceived usefulness having the most immediate and major effect on satisfaction. Conclusions: The findings are critical in determining students’ satisfaction and preparedness to continue with MOOCs. Consequently, educational reforms should be tailored accordingly.